The Virtual Meets the Real in Sports World: Is There a Circular Effect Between Traditional Sports and eSports Fan Identification? - Andre Ferreira Gavinho Cardoso; Victor Manoel Cunha de Almeida (BBR: Brazilian Business Review)
This study was designed to investigate the influence of eSports fan identification on traditional sports teams and vice-versa, specifically in cases where there is an intersection of soccer teams and the eSports world. The Points of Attachment Index was applied with the theoretical background used mainly being the Social Identity Theory (Tajfel & Turner, 1979). Four substantive hypotheses were translated into a conceptual model. Surveys were collected during eSports events in the city of Rio de Janeiro in 2019. Valid questionnaires collected reached 1,420. Data analysis was completed by applying descriptive analysis, exploratory factor analysis, and confirmatory factor analysis, to verify the reliability of the constructs, as well as the convergent and discriminant validity. The Structural Equation Modeling technique was used to test the substantive hypotheses. The empirical outcomes suggest that the identification of a fan with a soccer club exerts a positive influence on the identification of the fan with the club’s eSports team, but the opposite cannot be stated.